Integrating Homeopathy at the Holistic Level - Chauhan, Dinesh (Homœopathic Links, 2013)
The observation of expressions at the holistic level is the long-sought missing link between classical Hahnemannian homeopathy and contemporary classical homeopathy. In my view, this bridges the gap and integrates all classical homoeopaths, thereby clearing up all ambiguity.
Keywords: Individualistic expressions at the holistic level; Missing link; Traditional schools of homeopathy; Contemporary schools of homeopathy; Hahnemann; Kent; Essence; Human core; Synergy; integrating